Key factors affecting psychosocial well-being in thalassemic children from eastern India: an institutional study - Saha, Rajib (International Journal of Research in Medical Sciences, 2024)
Background: Thalassemia syndromes, prevalent in Eastern India, significantly impact the psychosocial health of affected children. The challenges associated with chronic treatment and disease management underscore the need for comprehensive quality of life assessments. Methods: This cross-sectional study was conducted at Bankura Sammilani Medical College and Hospital from July 2022 to June 2023. A sample of 371 thalassemic children aged 5-12 was analyzed using the Pediatric Quality of Life Inventory 4.0 Generic Core Scale. Socio-demographic data and psychosocial health were evaluated through parent interviews and clinical records. Statistical analyses included correlation and regression models to identify factors influencing psychosocial health. Results: The mean psychosocial health summary score was 63 (SD=9.4), indicating significant psychosocial challenges. Key factors associated with better psychosocial outcomes included lower duration of blood transfusions, female gender, positive family history of thalassemia, and higher socioeconomic status. The regression analysis revealed that these factors collectively explained 21.3% of the variability in psychosocial health scores. Conclusion: The study emphasizes the critical influence of gender, family history, socioeconomic status, and transfusion duration on the psychosocial well-being of thalassemic children. Integrated care approaches combining medical treatment with psychological support are essential for improving quality of life. Early intervention strategies, family support programs, and tailored treatment plans that consider gender-specific needs are recommended to address the emotional and social challenges faced by these children.